Formação seminarística na perspectiva do intelectual orgânico dos pobres no século XXI: limites e possibilidades - Cordeiro, Elcio Alcione (2020)
This research aimed to analyze seminary training from the perspective of the organic intellectual of the poor. We start from the historical analysis of the thinker Antônio Gramsci (1891-1937) on the organic and traditional intellectual category of the Catholic Church as an analysis tool for seminary formation in the 21st century, from the perspective of the organic intellectual of the poor. Then, we present a historical period in which part of the Church of Latin America committed itself towards the poor through Liberation Theology. From this historical route, we analyze the limits and possibilities of seminary training for the option of the poor in the latest documents of the Church in the formative dimension of seminaries. For this, we propose the following objective: Analyze the 21st century seminary training proposal from the perspective of the organic intellectual of the poor, in the main documents of the Church, on seminary formation, verifying the limits and possibilities of this formative praxis. As a methodology, we use or focus on bibliographic and documentary research, using Gramsci's own texts as a source, basic writings from the perspective of Liberation Theology and the documents that support the formation proposal in Catholic seminaries. We conclude that it is possible to bring together Gramsci, Liberation Theology and the main documents of the formation of the seminary to form a social-religious leader of preferential option for the simple. The dialogue between Gramsci, Liberation Theology and seminary formation contributed to the formation of religious or nonreligious intellectuals. Finally, this is a research that sought in other currents of thought, such as Gramsci and Support Liberation Theology, contribution and approximation to the formation of the seminar present in the last documents of the Catholic Church that proposed the formation of the organic intellectual of the poor.